Cooperative Hydrogen Bonding in Glyco–Oligoamides: DNA Minor Groove Binders in Aqueous Media. Issue 52 (30th October 2014) - Blázquez‐Sánchez, M. Teresa; Marcelo, Filipa; Fernández‐Alonso, M. Carmen; Poveda, Ana; Jiménez‐Barbero, Jesús; Vicent, Cristina
Abstract A strategy to create cooperative hydrogen‐bonding centers by using strong and directional intramolecular hydrogen‐bonding motifs that can survive in aqueous media is presented. In particular, glyco–oligoamides, a family of DNA minor groove binders, with cooperative and non‐cooperative hydrogen‐bonding donor centers in the carbohydrate residues have been designed, synthesized, and studied by means of NMR spectroscopy and molecular modeling methods. Indeed, two different sugar moieties, namely, β‐D‐Man‐Py‐γ‐Py‐Ind (1; Ind=indole, Man=mannose, Py=pyrrole) and β‐D‐Tal‐Py‐γ‐Py‐Ind (2; Tal=talose), were chosen according to our design. These sugar molecules should present one‐ or two‐directional intramolecular hydrogen bonds. The challenge has been to study the conformation of the glyco–oligoamides at low temperature in physiological media by detecting the exchangeable protons (amide NH and OH resonances) by means of NMR spectroscopic analysis. In addition, two more glyco–oligoamides with non‐cooperative hydrogen‐bonding centers, that is, β‐D‐Glc‐Py‐γ‐Py‐Ind (3; Glc=glucose), β‐D‐Gal‐Py‐γ‐Py‐Ind (4; Gal=galactose), and the model compounds β‐D‐Man‐Py‐NHAc (5) and β‐D‐Tal‐Py‐NHAc (6) were synthesized and studied for comparison. We have demonstrated the existence of directional intramolecular hydrogen bonds in 1 and 2 in aqueous media. The unexpected differences in terms of stabilization of the intramolecular hydrogen bonds in 1 and 2 relative to 5 and 6 promoted us to evaluate the influence of CH—π interactions on the establishment of intramolecular hydrogen bonds by using computational methods. Initial binding studies of 1 and 2 with calf‐thymus DNA and poly(dA‐dT)2 by NMR spectroscopic analysis and molecular dynamics simulations were also carried out. Both new sugar–oligoamides are bound in the minor groove of DNA, thus keeping a stable hairpin structure, as in the free state, in which both intramolecular hydrogen‐bonding and CH—π interactions are present.